Incidence and Outcomes of Sepsis in Korea: A Nationwide Cohort Study From 2007 to 2016. Issue 12 (December 2019) - Oh, Seung-Young; Cho, Songhee; Kim, Ga Hee; Jang, Eun Jin; Choi, Seongmi; Lee, Hannah; Ryu, Ho Geol
Abstract : Objectives: This study aimed to estimate the incidence and clinical outcomes of sepsis in Korea from 2007 to 2016. Design: Retrospective observational study. Setting: Nationwide study with population-based healthcare reimbursement claims database. Patients: Using data from the National Health Insurance Service of Korea, patients who were hospitalized with a diagnosis of sepsis from 2007 to 2016 were analyzed. The incidence of sepsis was calculated using mid-year census population and analyzed according to year, age, and sex. The Elixhauser Comorbidity Index score was calculated to adjust for the impact of comorbidities on clinical outcome. In-hospital mortality, hospital length of stay, ICU admission rates, and risk factors for in-hospital mortality were also analyzed. Interventions: None. Measurements and Main Results: The incidence of sepsis increased from 173.8 per 100, 000 population in 2007 to 233.6 per 100, 000 population in 2016. In-hospital mortality decreased from 30.9% in 2007 to 22.6% in 2016 ( p < 0.0001). From 2007 to 2016, hospital length of stay and ICU admission rates associated with sepsis decreased from 26.0 ± 33.5 days to 21.3 ± 24.4 days ( p < 0.0001) and from 16.2% to 12.7% ( p < 0.0001), respectively. Male sex, age greater than 50 years, Elixhauser Comorbidity Index greater than 10, and mechanical ventilation were identified as risk factors for in-hospital mortality after adjusting for baseline characteristics. Conclusions: The incidence of sepsis in Korea increased from 2007 to 2016, while the associated in-hospital mortality, hospital length of stay, and ICU admission rates decreased. Abstract : Supplemental Digital Content is available in the text.